Gate-to-gate life cycle assessment of lithium-ion battery recycling pre-treatment - Anna Pražanová; Michael Fridrich; Jan Weinzettel; Vaclav Knap (Cleaner Environmental Systems)
Recycling spent lithium-ion batteries (LIBs) is critical for enhancing environmental sustainability and resource conservation; however, the environmental and energy impacts of LIB recycling are not yet comprehensively understood due to the diverse applications of LIB cells and the variability in recycling technologies. This study presents a gate-to-gate life cycle assessment (LCA) of a recycling pre-treatment process at a small-scale plant in the Czech Republic, focusing on spent LIBs from electric vehicles (EVs) and consumer electronics cells (CECs). Using the SimaPro LCA software and the Ecoinvent 3.9 database, the analysis evaluated the environmental impact of recycling operations across several categories, including climate change, eutrophication, freshwater, and resource use, minerals and metals. The findings reveal that the recycling pre-treatment process for CECs achieves greater benefits in climate change mitigation compared to EV batteries, with a 5% lower impact for climate change associated with EV batteries relative to CECs. Moreover, the study highlights the effectiveness of optimized recycling practices in alleviating environmental burdens. A notable finding is the significance of secondary material recovery, particularly metals such as copper and aluminium, as these materials can substitute for primary raw materials, thereby minimizing resource use and reducing emissions. These aspects emphasize the need for high recovery efficiency to enhance environmental benefits. However, further research is essential to fully comprehend the environmental impacts of LIB recycling and to resolve uncertainties concerning battery composition and the effectiveness of different recycling technologies.